'A son who is a man:' receptive masculinity in Chinua Achebe's Things Fall Apart. Issue 4 (2nd October 2021) - Umezurike, Uchechukwu Peter
ABSTRACT: Chinua Achebe's Things Fall Apart narrates the contestations of performing masculinity in precolonial Nigeria. Employing ideas by Michael Slote and Judith Butler, I focus on Nwoye's character to show how Achebe deploys him to undermine social norms. Nwoye refuses to be a man in the traditional sense, thus enacting an alternative subjectivity in conflict with the hegemonic masculinity projected by his father. I argue that Achebe has created a character whose openness defines his relations with others in order to deemphasize the value placed on gender. Nwoye's embrace of receptivity positions him to reflect on the precariousness around him and identify with the marginalized in society, thus underscoring the perils of enacting and valorizing male hegemony. Achebe's depiction of receptive masculinity provides a means to reimagine and reconfigure modes of being a man, while reaffirming individual selfhood. This paper contributes to the growing scholarship on men and masculinities in postcolonial and African gender studies.